TLR2- and TLR3-activated microglia induce different levels of neuronal network dysfunction in a context-dependent manner - Schilling, Simone; Chausse de Freitas, Bruno; Dikmen, Hasan Onur; Almouhanna, Fadi; Hollnagel, Jan-Oliver; Lewen, Andrea; Kann, Oliver (Brain, behavior and immunity, 2021)
Recognition of pathogen- or damage-associated molecular patterns (PAMPs, DAMPs) by innate Toll-like receptors (TLRs) is central to the activation of microglia (brain macrophages) in many CNS diseases. Notably, TLR-mediated microglial activation is complex and modulated by additional exogenous and endogenous immunological signals. The impact of different microglial reactive phenotypes on electrical activity and neurotransmission is widely unknown, however. We explored the effects of TLR ligands on microglia and neuronal network function in rat organotypic hippocampal slice cultures (in situ), i.e., postnatal cortical tissue lacking adaptive immunity. Single exposure of slice cultures to TLR2 or TLR3 ligands [PGN, poly(I:C)] for 2-3 days induced moderate microglial activation featuring IL-6 and TNF-α release and only mild alterations of fast neuronal gamma band oscillations (30-70 Hz) that are fundamental to higher cognitive functions, such as perception, memory and behavior. Paired exposure to TLR3/TLR2 or TLR3/TLR4 ligands (LPS) induced nitric oxide (NO) release, enhanced TNF-α release, and associated with advanced network dysfunction, including slowing to the beta frequency band (12-30 Hz) and neural bursts (hyperexcitability). Paired exposure to a TLR ligand and the leukocyte cytokine IFN-γ enhanced NO release and associated with severe network dysfunction, albeit sensitive parvalbumin- and somatostatin-positive inhibitory interneurons were preserved. Notably, the neuronal disturbance was prevented by either microglial depletion or pharmacological inhibition of oxidant-producing enzymes, inducible NO synthase (iNOS) and NADPH oxidase. In conclusion, TLR-activated microglia can induce different levels of neuronal network dysfunction, in which severe dysfunction is mainly caused by reactive oxygen and nitrogen species rather than proinflammatory cytokines. Our findings provide a mechanistic insight into microglial activation and functional neuronal network impairment, with relevance to neuroinflammation and neurodegeneration observed in, e.g., meningoencephalitis, multiple sclerosis and Alzheimer’s disease.
Gesehen am 15.09.2021